How Preferences of General Medicine Students for Specialty Choice Are Affected? a qualitative study - Mehdi Heidari; Mahmoud Keivanara; Maryam Moeeni (Kerman University of Medical Sciences, 2019)
How Preferences of General Medicine Students for Specialty Choice Are Affected? a qualitative study   Heidari Mehdi1, Keivanara Mahmood2, Moeeni Maryam3*   1. MSc in Health Economics, School of Management & Medical Information Sciences, Isfahan University of Medical Sciences, Isfahan, Iran. 2. Professor of Medical Sociology, Social Determinants of Health Research Center, Isfahan University of Medical Sciences, Isfahan, Iran 3. Assistant Professor, Social Determinants of Health Research Center, Isfahan University of Medical Sciences, Isfahan, Iran * Corresponding Author: Maryam Moeeni Address: School of Management and Medical Information Sciences, Isfahan University of Medical Sciences, Hezar-Jerib Ave., Isfahan, Iran Tel: 0098 3137925125                                              Email: m_moeeni@mng.mui.ac.ir  Abstract: Background & Objectives: Equal distribution of human resources in health sectors was one of the main aspects of Alma-Ata Declaration (2000). Since physicians are among the skillful human resources in health sector, optimal allocation of medical specialties has been always a challenge for policy makers. Distribution of general medicine physicians and specialties is related to medical students' preferences for speciality choice. This study aimed to identify the factors affecting preferences in choosing medical specialty. Methods: This was a qualitative study based on the grounded theory. Through apllying snowball sampling, participants were selected from senior medical students of Isfahan University of Medical Sciences in the academic year 2016/2017and 28 interviews were conducted. Data analysis was done based on thematic analysis and applying MAXQDA18 software. Results: We extracted 4 main themes and 10 subthemes. Main themes included students' perception of the medical specialties, students' characteristics, medical specialties' characteristics, and social conditions.  Conclusion: In order to attract medical students to more needed medical specialities and optimal distribution of specialities, policy makers should consider both individual and social determinants of medical specialty choice.   Keywords: Preferences, Specialty careers, Primary care specialties, Medical students   Citation: Heidari M, Keivanara M, Moeeni M. How Preferences of General Medicine Students for Specialty Choice Are Affected? a qualitative study. Journal of Health Based Research 2019; 5(3): 303-18. [In Persian]